The Role and Mechanisms of Selenium Supplementation on Fatty Liver-Associated Disorder - Lin Xu; Yuanjun Lu; Ning Wang; Yibin Feng (Antioxidants, 2022)
Non-alcoholic fatty liver disease (NAFLD) is the most frequent chronic liver disease without effective therapy. Selenium, as an essential trace element for humans, is notable for its antioxidant properties. The previous study shows that selenium levels in NAFLD patients are lower than normal ones. Selenium supplementation can effectively alleviate metabolic disorders by relieving anti-oxidative stress and anti-inflammatory regulation. However, the correlation between selenium and NAFLD has not been fully clarified. Herein, we review the current studies on selenium in regulating the different stages of NAFLD and summarize relevant clinical trials to highlight the potential roles of selenium in NAFLD treatment.